Relative Bioavailability of a Single Dose of Belimumab Administered Subcutaneously by Prefilled Syringe or Autoinjector in Healthy Subjects. Issue 3 (4th December 2015) - Struemper, Herbert; Murtaugh, Thomas; Gilbert, Jane; Barton, Matthew E.; Fire, Joseph; Groark, James; Fox, Norma Lynn; Roth, David; Gordon, David
Abstract: Intravenous belimumab is approved for the treatment of systemic lupus erythematosus; subcutaneous self‐administration would enable greater patient access. This study assessed relative bioavailability, tolerability, and safety of 1 subcutaneous dose of self‐administered belimumab by healthy subjects using a single‐use autoinjector or prefilled syringe. Subjects (randomized 1:1:1:1) self‐administered belimumab 200 mg subcutaneously (abdomen or thigh) by prefilled syringe or autoinjector. Pharmacokinetics, adverse events (AEs), injection‐site pain, and administration errors were recorded. Of 81 subjects, 5 experienced administration errors and were excluded from pharmacokinetic analyses. Mean serum belimumab concentration profiles were similar for both devices, with a weak trend toward higher concentrations for thigh injection compared with abdominal injections. Maximum observed serum concentration was slightly higher with the autoinjector (27.0 vs 25.3 µg/mL) and area under the concentration–time curve slightly lower (701 vs 735 day · μg/mL), compared with the prefilled syringe. Incidence of AEs was 51% (41 of 81 subjects; headache was most common), with no serious or severe AEs. Median injection‐site pain scores were low (0 after 1 hour). Device handling was reported as acceptable by ≥95% of autoinjector users and ≥90% of prefilled syringe users for each characteristic assessed. These results support the use of either device for belimumab subcutaneous administration.